THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE ON AGGRESSIVE BEHAVIOR AMONG PRISONERS IN CLASS IIA CORRECTIONAL INSTITUTIONS PURWOKERTO - Putra, Dewa Armansyah; Anwar, Umar (PT Altin Riset Publishing, 2023)
The aim of this research is to understand whether there is an influence between emotional intelligence and spiritual intelligence on aggressive behavior in prisoners at the Class IIA Purwokerto prison. The research method used was quantitative, and the sample consisted of 67 prisoners involved in violations. Data analysis in this research was carried out using IBM SPSS 25 software. The test results showed that the R Square value was 0.330 or 33.0%, which means that emotional intelligence and spiritual intelligence together contributed 33% to aggressive behavior. The regression equation is Y = 84.201 - 0.87X1 - 0.258X2. The constant value (a) is 84.21, the emotional intelligence regression coefficient (b1) is -0.87, and the spiritual intelligence regression coefficient (b2) is -0.258. Based on these results, steps can be taken to provide psychological guidance to prisoners according to individual needs, with the aim of reducing aggressive behavior among prisoners.